Polemik Penerapan Metode Hermeneutik dalam Menafsir Alquran (Jurnal Riset Rumpun Agama dan Filsafat, 2024)
Investment is a type of economic activity. Behind all wealth there is zakat. If wealth is not used in a useful way, it can be taken away by zakat over time. One of the good things about zakat is that it encourages all Muslims to use their money in ways that are productive. Only the profits from investments are subject to zakat, not the assets themselves. Everyone should know about the ethics of investing to make sure they don’t invest in things that are not allowed in Islam. Not knowing about Islamic investment can lead people to make bad decisions and act in ways that go against Islamic law. The desire for big profits is one reason people might make wrong choices. Investment is a kind of business, and it has risks because it involves uncertain things, which can lead to uncertain or unstable results. Islam encourages people to take action and be prepared through investing. Putting money in an Islamic bank is also considered an investment because the outcome is not certain.